“When the bear won't go hunt”: masculinity in Shakespeare's Twelfth Night - Jean-Louis CLARET (E-REA)
In Twelfth Night by William Shakespeare, the character of Orsino stands for the male polarity, as opposed to Olivia who represents femininity. His interest in music, perfumes and love thoughts, his narcissism and his refusal to “go hunt,” contribute to making up a surprisingly ambiguous male icon. Orsino is even reminiscent of the “popinjay” who appears in 1 Henry IV. In fact Duke Orsino, the “little bear” described as “noble in nature as in name,” suffers from a love melancholy that has affected his male identity. Yet despite these assaults, Orsino remains a male figure in the eyes of the audience. His encounter with a young eunuch – a cross-dressed young woman – will enable him to reassert a masculinity he seemed to have lost sight of. The haunting figures of Narcissus and Echo find a strange echo in the main characters who prove particularly resilient and clearly subservient to the structural requirements of the comedy. Twelfth Night invents new polarities that, like some of the characters, are not what they are.